2002
DOI: 10.1177/0739986302238211
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know about Latino Drug Use? Methodological Evaluation of State Databases

Abstract: This study has two goals, to estimate drug use trends among Latino adolescents in states where the majority reside, and evaluate methodologies used to gather this information to improve their quality. State surveys provide the only source of estimates of drug use by ethnic groups at this geographic level. Presumably, these data are used to evaluate national drug control policies, target research and prevention, and law enforcement efforts. This study compares survey data from Monitoring the Future (national U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…born criminal justice clients were also more likely to report both lifetime and recent drug use than foreign born criminal justice clients. Our findings regarding drug use is also similar to previous studies of the general population that found U.S. born Latinos report more drug use than foreign born Latinos [42]. Although the U.S. born criminal justice clients were more likely to report lifetime drug use than foreign-born criminal justice clients, there were few differences in recent drug use.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…born criminal justice clients were also more likely to report both lifetime and recent drug use than foreign born criminal justice clients. Our findings regarding drug use is also similar to previous studies of the general population that found U.S. born Latinos report more drug use than foreign born Latinos [42]. Although the U.S. born criminal justice clients were more likely to report lifetime drug use than foreign-born criminal justice clients, there were few differences in recent drug use.…”
Section: Discussionsupporting
confidence: 89%
“…To the authors knowledge, there are no studies that compare drug use behavior and mental health between foreign-born and U.S. born Latino community correction clients. However, in the general population, drug use seems to be higher among U.S. born than foreign-born Latino youth [42], and U.S. born Latinos also have a lower perception of drug use as a risky behavior [43]. …”
Section: Introductionmentioning
confidence: 99%
“…A consistent finding in Hispanic drug use research has been that U.S. born Hispanics report higher rates of experimental drug use, abuse and dependence than Hispanic immigrants (Vega, Gil, and Kolody, 2002;Alvarez and Ruiz, 2001;De la Rosa, Khalsa, and Rouse, 1990). However, qualitative studies and epidemiological evidence of substance abuse 1 among populations living on the US-Mexico Border are sparse (Strathdee, S.A., et al, 2007;Wallisch and Spence, 2006;Frost et al, 2006;Ramos, B Ferreira-Pinto, and Ramos, 1998;Amaro, 2000;Vega et al, 1998).…”
Section: Introductionmentioning
confidence: 92%
“…Although increasingly more research is appearing on substance use among Hispanics in the United States (e.g., Warner et al, 2006;Maxwell, 2006;Patterson et al, 2006;Wallisch and Spence, 2006;Deren, Shedlin and Decena, 2005;Shedlin, Decena, and Oliver-Velez, 2005;Vega, Gil, and Kolody, 2002;Alvarez and Ruiz, 2001;Berk et al, 2000;De la Rosa, Khalsa, and Rouse, 1990), qualitative and epidemiological data on substance use among populations living on the U.S.-Mexico Border are sparse (Wallisch and Spence, 2006;Frost, et al, 2007;Ramos, Ferreira-Pinto, and Ramos, 1998). Given national, state, and local discourse on immigration reform and its impact on immigrants with substance user treatment needs, research that contributes to understanding how immigration policies are perceived by immigrants and how such policies affect their utilization of substance user treatment programs is needed.…”
Section: Definition Of the Problemmentioning
confidence: 99%
“…For instance, a body of literature has documented the existence of the “immigrant paradox,” or the tendency for Hispanics who were born in other countries to have more favorable health outcomes than those who were born in the United States (Prado, Szapocznik, Schwartz, Maldonado-Molina, & Pantin, 2008; Schwartz, Unger, Zamboanga, & Szapocznik, 2010). Several explanations for this phenomenon have been proposed, including the deterioration of Hispanic cultural and family values, and increased exposure to risk behavior in the United States (Prado et al, 2008; Vega, Gil, & Kolody, 2002). Because ecological and proximal risk factors may operate differently between U.S.- and foreign-born youth and young adults, an evaluation of the generational differences in IPV among Hispanics is warranted.…”
Section: Introductionmentioning
confidence: 99%